Statement by the Managing Director on the Work Program of the Executive Board. (Policy Papers; Policy Paper ;, 2018)
This Work Program (WP) translates the strategic directions and policy priorities laid out in the Fall 2018 Global Policy Agenda and the International Monetary and Financial Committee Communique into an Executive Board agenda for the next twelve months. Its main policy priorities and deliverables are as follows: -- Advise member countries to rebuild buffers, enhance resilience, and advance structural reforms for the benefit of all to respond to mounting vulnerabilities. The Spring 2019 World Economic Outlook (WEO) will analyze the macroeconomic implications of increased corporate market power. The Global Financial Stability Report (GFSR) will discuss global financial risks in light of tightening financial conditions, while the Fiscal Monitor (FM) will study how improved governance in fiscal frameworks and institutions can reduce corruption vulnerabilities and improve policy outcomes. -- Promote cooperation to modernize the multilateral trade system and address other challenges that transcend borders. The spillover chapter of the Spring 2019 WEO will examine the determinants of trade imbalances and spillovers from different trade policies. Building on the 'Bali Fintech Agenda," staff will provide a stock-take of fintech developments and study the implications for cross-border flows, financial integrity, and global monetary and financial stability in Fintech: The Experience So Far. To support Japan's G-20 Presidency, staff will prepare a note on Macroeconomic and Fiscal Implications of Aging. -- Adapt the Fund's policy toolkits to further enhance its surveillance, lending, and capacity development. Scoping notes for the Surveillance Review and the Financial Sector Assessment Program (FSAP) Review will establish priorities. The Review of Conditionality and the Design of Fund Supported Programs will assess the effectiveness of Fund program design and conditionality. Building on an earlier paper, the Review of Facilities for Low-Income Countries-Reform Proposals will offer proposals on adjusting these facilities to better meet evolving membership needs. The Fund will implement a multipronged approach to enhance debt transparency and sustainable financing practices. Staff will also strengthen debt sustainability analysis by reviewing the Debt Sustainability Framework for Market Access Countries and the Fund's Debt Limits Policy. The Revised IMF Policies and Practices on Capacity Development will reflect on suggestions made in recent discussions. -- Improve governance of the Fund and modernize its operations. Work on the 15thGeneral Review of Quotas will continue with a view to completing it by the Spring Meetings, and no later than the Annual Meetings, of 2019. The Board will receive a briefing on Modernizing HR Policies and Practices: A Progress Report on Key Initiatives and continue the discussions on the Comprehensive Compensation and Benefits Review.